A comparative assessment of in vitro cytotoxic activity and phytochemical profiling of Andrographis nallamalayana J.L.Ellis and Andrographis paniculata (Burm. f.) Nees using UPLC-QTOF-MS/MS approach. Issue 57 (8th November 2021) - Goel, Narender; Gajbhiye, Rahul L.; Saha, Moumita; Nagendra, Chennuru; Reddy, Araveeti Madhusudhana; Ravichandiran, V.; Das Saha, Krishna; Jaisankar, Parasuraman
Abstract : A comparative study of two Andrographis species have been done, and it was found that Andrographis nallamalayana J.L.Ellis is phytochemically and biologically different from Andrographis paniculata (Burm. f.) Nees. Abstract : Andrographis paniculata (Burm. f.) Nees and Andrographis nallamalayana J.L.Ellis have traditionally been used to treat various ailments such as mouth ulcers, intermittent fever, inflammation, snake bite. This study compares the comparative in vitro cytotoxic activity, and phytochemical profiling of methanol extract of A. nallamalayana (ANM) and A. paniculata (APM). UPLC-ESI-QTOF-MS/MS analysis has been performed. The cytotoxic activity of crude methanol extracts were evaluated against three different cancer cell lines (HCT 116, HepG2, and A549 cell line). Both plants' extract exhibited significant cytotoxic activity against tested cell lines in a dose-dependent manner. IC50 of ANM and APM in HCT 116 cell was 11.71 ± 2.48 μg ml −1 and 45.32 ± 0.86 μg ml −1 and in HepG2 cell line was 15.65 ± 2.25 μg ml −1 and 60.32 ± 1.05 μg ml −1 respectively. Cytotoxicity of these two extracts was comparatively similar in A549 cells. ANM induced cytotoxicity involved programmed cell death, externalisation of phosphatidylserine, ROS generation, up-regulation and down-regulation of major apoptotic markers. HRMS analysis of ANM and APM resulted in the identification of 59 and 42 compounds, respectively. Further, using the MS/MS fragmentation approach, 20 compounds, of which 18 compounds were identified for the first time from ANM, which belongs to phenolic acids, flavonoids, and their glycosides. Three known compounds, echioidinin, skullcapflavone I and 5, 2′, 6′-trihydroxy-7-methoxyflavone 2′- O -β-d -glucopyranoside, were isolated from A. nallamalayana and their crystal structures were reported for the first time. Subsequently, seven major compounds were identified in A. nallamalayana by direct comparison (retention time and UV-spectra) with authentic commercial standards and isolated compounds using HPLC-UV analysis. The cytotoxicity of phytochemicals from both the plants using in silico tools also justify their in vitro cytotoxic activity. It is the first report on the comparative characterisation of phytochemicals present in the methanolic extract of both the species of Andrographis, along with the cytotoxic activity of A. nallamalayana .